OBLITERATIVE VASCULAR DISEASES, OBLITERATIVE ENDARTERITIS, AND MODERN TREATMENT METHODS - Suyunov Og‘abek Oybek o'g’li (Web of Journals Publishing, 2024)
The latest achievements and innovative approaches in the field of medicine have significantly expanded the possibilities for effective treatment of these diseases. Types of obliterative vascular diseases, causes, diagnostic methods, and the most modern treatment methods.
Keywords: Obliterative vascular diseases, Obliterative Endarteritis, Thromboangiitis obliterans, Doppler Ultrasound, MRA and CTA